2022
DOI: 10.3389/fphys.2022.1040809
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional relationship between AMPK pathway activation and myokine secretion in skeletal muscle: How it affects energy metabolism

Abstract: Myokines are peptides and proteins secreted by skeletal muscle cells, into the interstitium, or in the blood. Their regulation may be dependent or independent of muscle contraction to induce a variety of metabolic effects. Numerous myokines have been implicated in influencing energy metabolism via AMP-activated protein kinase (AMPK) signalling. As AMPK is centrally involved in glucose and lipid metabolism, it is important to understand how myokines influence its signalling, and vice versa. Such insight will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 188 publications
0
0
0
Order By: Relevance
“…AMPK plays an important role in maintaining cellular energy homeostasis; however, excessive AMPK activation leads to muscle atrophy due to decreased muscle protein synthesis through inhibition of the mTOR signaling pathway [ 11 , 12 , 14 ]. Our results showed that differentiated C2C12 myotubes were atrophied following treatment with AICAR, an AMPK inducer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMPK plays an important role in maintaining cellular energy homeostasis; however, excessive AMPK activation leads to muscle atrophy due to decreased muscle protein synthesis through inhibition of the mTOR signaling pathway [ 11 , 12 , 14 ]. Our results showed that differentiated C2C12 myotubes were atrophied following treatment with AICAR, an AMPK inducer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that AMP-activated protein kinase (AMPK), which plays an important role in muscle metabolism and transcriptional regulation, is involved in muscle wasting [ 10 - 12 ]. AMPK is a regulator of protein catabolism and anabolism, and excessive AMPK activity results in muscle loss and decreased mammalian target of rapamycin (mTOR) signaling [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential explanation for the rescue produced by octopamine feeding is that exogenous octopamine may act on peripheral clocks, like those in the muscle, to rescue peripheral rhythms that may be involved in the metabolic changes required in muscle to produce benefits from exercise [55]. Release of myokines from muscle has been shown to be important for the metabolic changes that occur in other body tissues to allow for adaptations to exercise, and Drosophila OA receptors have been shown to be required for exercise-induced changes in other tissues, suggesting OA must regulate secondary messengers emanating from muscle [56]. Further supporting this idea, OA has recently been shown to upregulate expression of a putative myokine in flies, the FNDC5/Irisin homolog Iditarod [57].…”
Section: Discussionmentioning
confidence: 99%